Development of a Pocket Book with Islamic Nuances Based on HOTS and Contextual Pythagorean Theorem - Andini, Zayla Agatri; Andhany, Ella (Unnes Journal of Mathematics Education, 2023)
This research was a type of development research. The objective of this research aimed to develop pocket books with Islamic nuances based on HOTS (High Order Thinking Skills) and contextual material on the Pythagorean theorem and know how the feasibility, effectiveness, and practicality of pocket books with Islamic nuances with HOTS-based and contextual material on the Pythagorean theorem. The research model used in this study was the 4-D model. Data collection techniques used in stages were observation, interviews, questionnaire instruments from material experts and media experts, as well as teacher and student responses to HOTS-based and contextual pocket books and test instruments. The results of this study are in the form of pocket books with Islamic nuances based on HOTS and contextual material on the Pythagorean theorem that is feasible, effective, and practical.